Utilization of De-Oiled Spent Bleaching Clay as a Catalyst for Transesterification of Palm Olein - Rehan, Zainol Abidin; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim (2015)
The awareness o fossil oil depletion, fluctuating oil price and environmental concerns has intensified the search for an alternate fuel. Biodiesel fuel is produced catalytically by transesterification reaction here catches the researcher attention nowadays as it is a promising alternative diesel fuel (Xie and Yang, 2012). Edible oil industries produce spent bleaching clay (SBC) as their major wastes. Biodiesel is prepared via a catalytic reaction between triglycerides and alcohol. Glycerol is the by-product of the reaction. The reaction involves the breakage of the glycerol structure and exchanges of alkyl group between the alcohol and ester part of the triglycerides molecule; as such, the reaction is known as transesterification (Alba-Rubio et al., 2010). Among the three major routes, transesterification seems to be the best compared to heating and microemulsions for reducing the viscosity as well as minimizing engine complications (Feyzi et al., 2014). Other than that, the transesterification pathway, esterification of free fatty acids (FFAs) with alcohols in the presence of acid catalysts also produces methyl esters or biodiesel. One of the main reasons or the conceptualization of biodiesel is the environmental pollution, specifically CO2 emission. Concerning the CO2 emission, in 2005 the EU introduced an innovative cost-effective scheme termed the ‘Emission Trading Scheme’ (ETS), a scheme that Australia, New Zealand and the United States are keen to adopt in their long-term plan for dealing with greenhouse gases (Narkhede et al., 2014). Over the years, extensive research have been carried out in transesterifying various type of oils such as palm oil, cottonseed oil, soybean oil, tobacco seed oil and tea seed oil using basic catalysts into biodiesel (Xie and Wang, 2013). Bleaching clay is used in palm oil refinery to remove colouring matters, soap, gums, metals (iron, nickel), oxidized compounds and polymers. Reports indicated that bleaching clay retains 20-40% of oil and importantly, the absorbed oil represents the major part of bleaching cost. In Malaysia itself, with CPO production of 17.7 million tonnes in 2008, annually 177 000 tonnes of SBC is generated, at 1% clay dosage, which translates to nearly 50 000 tonnes of adsorbed oil (at 28% oil retention). This oil-laden SBC is currently under utilized by dumping the oil-laden SBC undoubtedly creates environmental complications. As such any efforts to utilize the adsorbed waste oil reduce bleaching cost; add value to SBC as well as environmental gain. The other advantage of using SBC oil. In additional to that, the deoiled clay can be reused. In short, utilizing SBC for biodiesel production has many merits (Boey et al., 2011). In this work, an environmental friendly transesterification reaction using de-oiled spent bleaching clay (D-SBC) loaded with KOH is being developed. The catalyst loaded with 40% KOH on D-SBC using wet impregnation method followed by calcinations at 600°C for 4 hours was seems to give highest basicity and the best catalytic activity for transesterification. The catalyst was undergoing characterization by means of FTIR, XRD, BET, XRF, FE-SEM and Hammet indicator test. FESEM image of the catalyst is clearly shown in Figure 1. The effect of reaction parameters was then studied such as methanol to oil molar ratio, reaction time and catalyst amount. The reaction conversion of 8.57% was achieved under the optimum condition. Utilization of D-SBC as an eco-friendly and cheap solid support is a promising. Therefore, progress should be made on doping more other metals on D-SBC for transesterification of oil with methanol